1988
DOI: 10.3109/10826088809039203
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Physical and Sexual Abuse and Tobacco, Alcohol, and Illicit Drug Use Among Youths in a Juvenile Detention Center

Abstract: The relationships between child physical and sexual abuse and tobacco, alcohol, and illicit drug use are little understood and underinvestigated. Data gathered from a study of youths in a regional detention center permitted an examination of this issue. The results indicate that the youths' physical and sexual abuse experiences are significantly and positively related to their use of illicit drugs. The implications of these findings for further research are drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 11 publications
1
42
0
1
Order By: Relevance
“…The study by Green et al (1989) is a fine example of the use of multivariate techniques to assess the relative contributions of trauma exposure, pretraumatic factors, and posttraumatic factors to the prediction of alcohol abuse in combat veterans. Similarly, Dembo and colleagues (e.g., Dembo et al, 1988Dembo et al, , 1992 have effectively used structural equation modeling techniques to study the potential causal relationship of abuse histories, other family background characteristics, and the development of alcohol problems in adolescents. Such research has demonstrated that trauma exposure contributes unique variance to the prediction of alcohol abuse, over and above the effects of other relevant variables.…”
Section: Sample Selection Concernsmentioning
confidence: 99%
“…The study by Green et al (1989) is a fine example of the use of multivariate techniques to assess the relative contributions of trauma exposure, pretraumatic factors, and posttraumatic factors to the prediction of alcohol abuse in combat veterans. Similarly, Dembo and colleagues (e.g., Dembo et al, 1988Dembo et al, , 1992 have effectively used structural equation modeling techniques to study the potential causal relationship of abuse histories, other family background characteristics, and the development of alcohol problems in adolescents. Such research has demonstrated that trauma exposure contributes unique variance to the prediction of alcohol abuse, over and above the effects of other relevant variables.…”
Section: Sample Selection Concernsmentioning
confidence: 99%
“…c) substance abuse (Dembo et al, 1988;Rohsenow, Corbett & Devine, 1988;Singer, Petchers & Hussey, 1989); d) involvement in prostitution (Bagley & Young, 1987;Silbert & Pines, 1981); e) sexual confusion and sexualized behaviors (Johnson & Shrier, 1985; f) eating disorders (Hambidge, 1988;Hall et al, 1989;Golfarb, 1987); and, g) delinquency: (Burgess, Hartman & McCormack, 1987;Smith, 1988;Eisenman, 1993).…”
Section: Outcomes Related To Sexual Abusementioning
confidence: 99%
“…Few studies have assessed the association between childhood abuse and smoking among adults [34][35][36] or adolescents. [37][38][39] Some studies have found associations of childhood abuse with substance and alcohol abuse but only marginal associations with cigarette smoking. 37,38 We found that the relationship between the number of categories of adverse childhood experiences and each of the smoking behaviors is strong and cumulative.…”
Section: Commentmentioning
confidence: 99%